PENGARUH BRAND EXPERIENCE, BRAND IMAGE DAN PERSEPSI KUALITAS TERHADAP BRAND LOYALITY MELALUI MEDIASI BRAND TRUST - Prasetyo, Arif Hadi; Suciningtyas, Santi; Ningsih, Diah Wuriah (Magister Manajemen STIE Bank BPD Jateng, 2024)
The purpose of this study was to determine the effect and analysisi of Brand Experience, Brand Image and Quality Perception on Brand Loyality with Brand Trust as an intervening variable. In this study using purposive sampling and accidental sampling of 100 respondents. The testing in this study was carried out by testing the validity, reliability, classical assumptions, testing the hypothesis in the form of a t test, multiple linear regression analysis, coefficient of determination, path analysis and sobel test. The results of the validity test of each variable question item are valid. The results of the reliability test on each variable question item are reliable. The classic assumption test results for each variable meet the classic assumption test criteria. The results of multiple linear regression analysis in this study obtained b1 = 0,192 indicating a positive effect of the Brand Experience variable (X1) on Brand Loyality (Y), b2 = 0,432 indicating a positive influence of the Brand Image variable (X2) on Brand Loyality (Y), b3 = 0,239 indicates a positive influence of Quality Perception variable (X3) on Brand Loyality (Y), b4 = 0,189 indicates a positive influence of Brand Trust variable (Z) on Brand Loyality (Y). For hypothesis testing, there is a partially significant effect between Brand Experience (X1) on Brand Loyality (Y) with tcount > ttable (2,364 > 1,984), Brand Image (X2) has a partially significant effect on Brand Loyality (Y) with tcount > ttable (4,770 > 1,984), Quality Perception (X3) has a partially significant effect on Brand Loyality (Y) with a tcount > ttable (4,173 > 1,984), Brand Trust (Z) ) has a partially significant effect on Brand Loyality (Y) with a value tcount > ttable (2,246 > 1,984). Brand Trust (Z) mediates the effect between Brand Experience (X1) on Brand Loyality (Y) with tcount > ttable (2,719 > 1,984), Brand Trust (Z) mediates the effect between Brand Image (X2) on Brand Loyality (Y) with a value tcount > ttable (3,230 > 1,984), Brand Trust (Z) mediates the influence between Quality Perception (X3) on Brand Loyality (Y) with a tcount > ttable (2,122 > 1,984)